Optimizing sample collection methods for detection of respiratory viruses in poultry housing environments. Issue 5 (14th April 2022) - Mo, Jongseo; Stephens, Christopher B.; Jordan, Brian; Ritz, Casey; Swayne, David E.; Spackman, Erica
Abstract: Viral respiratory diseases, such as avian influenza, Newcastle disease, infectious bronchitis and infectious laryngotracheitis, have considerable negative economic implications for poultry. Ensuring the virus‐free status of premises by environmental sampling after cleaning and disinfection is essential for lifting a quarantine and/or safely restocking the premises following an outbreak. The objectives of this study were to identify optimal sample collection devices and to determine the locations in poultry housing which are best for poultry respiratory virus sample collection. Chickens exposed to infectious bronchitis virus, which was used as a representative virus for enveloped poultry respiratory viruses, were housed in floor‐pens in either a curtain‐sided wood framed house or a cement block house. Foam swabs, cellulose sponges, polyester swabs, dry cotton gauze and pre‐moistened cotton gauze were evaluated for comparative efficiency in recovering viral RNA. Cotton gauze pre‐moistened with the viral transport media had the highest sensitivity among the devices (wood‐framed house: 78% positive, geometric mean titre [GMT] of 2.6 log10 50% egg infectious doses [EID50 ] equivalents/ml; cement block houses: 55% positive, GMT of 1.7 log10 EID50 equivalents/ml). Targeting virus deposition sites is also crucial for efficient virus elimination procedures and subsequent testing; therefore, 10 locations within the houses were compared for virus detection. In both housing types, the highest viral RNA loads were recovered from the tops of drinker lines within the pen. Places the chickens could contact directly (e.g., feeder rim) or were contacted by caretaker feet (hallway floor) also yielded higher levels of viral RNA more consistently. These results will facilitate the establishment of efficient environmental sampling procedures for respiratory viruses of poultry.